The Value of Measurment of Bilirubin in Pleural Fluid in the Differentiation between Exudative and Transudative Pleual Effusion (Medico Legal Update, 2021)
Background: The pleural effusion is a common clinical problem which can be exudative or transudativein nature due to variety of causes. Measurement of biochemical markers in the pleural fluid is an importantmeasure to distinguish exudative from transudative effusion.Aim of the Study: Is to determine the value of pleural fluid to serum bilirubin ratio to differentiate betweentransudative and exudative pleural effusion.Patients and Method: Thirty-five patients enrolled in this study, they admitted to medical ward in Baghdadteaching hospital and submitted to clinical, radiological, ultrasonographic examination proved to havepleural effusion from December 2018 to July 2019. Samples of blood and pleural fluid aspirated in themedical ward, analyzedafter 30-60 minute of aspiration. The sample of some cases were analyzed in privatelaboratories. Serum protein, total serum bilirubin and other investigation according to the condition of thepatient like blood urea, serum creatinine, liver function test, sputum of AFB. Pleural fluid analyzed fromprotein, total bilirubin, cell count, differential and cytology .Pleural biopsy was done to patients suspectedto have malignant or tuberculous effusion and grouped at the end of their hospitalization into exudativeand transudative effusion according to specific etiology, clinical examination, radiological finding, andthen measure the pleural fluid to serum protein ratio, pleural fluid to serum bilirubin for each patient. Wedepended on pleural fluid to serum protein ratio to compare with pleural fluid to serum bilirubin ratio fordifferentiation between exudative and transudative pleural fluid.Results: Twenty two patients with exudative effusion and thirteen patients were having transudate accordingto pleural fluid to serum protein (Light ’s criteria). P-value= 0.002, Fisher. Exact test= 0.001. Twenty threepatients with exudative effusion and twelve patients with transudative effusion according to pleural fluidto serum bilirubin ratio. P value= 0.37, Fisher. Exact test = 0.45. Pf/s ratio can increase the sensitivity andspecificity of Light ‘s criteria.Conclusions: Pleural fluid to serum bilirubin ratio can’t replace Light’s criteria in differentiation betweenexudates and transudate pleural effusion. Pf/s bilirubin ratio is a reliable test can easily perform but notcommon use in our hospital because of its costy and not familial use in our laboratories.